Autoimmune murine thyroiditis. V. Genetic influence on the disease in BSVS and BRVR mice - Rose, N. R. (1973)
Two inbred strains of mice, BSVS and BRVR, are similar in their antibody response to thyroglobulin but differ significantly with respect to thyroid gland damage. F(1) hybrids, like BSVS mice, respond well to thyroglobulin, exhibiting extensive thyroid lesions, whereas BRVR mice show minimal thyroid damage. H-2 typing of the two strains showed that BSVS mice have a type similar to H-2(th), with the H-2D-end of H-2(d) and the H-2K-end of H-2(s), whereas BRVR mice are H-2(k). The cellular response to thyroglobulin appears to be influenced by a specific immune response gene located near the K-end of the H-2 complex.